Sistem Pendukung Keputusan Pengembangan Ekowisata Mangrove Potensial Menggunakan Simple Additive Weighting (SAW) - Yerik Afrianto Singgalen (Journal of Computer System and Informatics (JoSYC), 2023)
Adjusting resource availability and traveler preferences will allow for an objective assessment of prospective mangrove ecotourism growth. In order to build mangrove ecotourism destinations effectively, it is vital to identify their priority locations. It is required to create the development program as a criterion and the development zone as a prioritized alternative in light of this. This study used the Simple Additive Weighting (SAW) technique, which includes the following stages: deciding on criteria and alternatives; weighing the relative importance of each criterion; creating a matrix of findings; and ranking the alternatives based on the biggest value. The study's findings indicate that five criteria can be categorized based on benefit and cost with varying relative values: attraction (benefit), ancillary (benefit), accommodation (cost), accessibility (cost), and amenities (cost). Attraction has a relative value of 0.3, ancillary has a relative value of 0.2, and amenities (cost) has a relative value of 0.15. The ranking results showed that the amenity criteria came first, followed by accessibility, then attractions, lodging, and ancillary. Attractions were ranked third, while accommodations came in fourth. This demonstrates the necessity for amenities that pique tourist interest and accessibility through accessible modes of transportation, informational resources, and roads to tourist destinations to support the growth of mangrove ecotourism special interest tourism. The management of mangrove ecotourism destinations can be improved by offering lodging options. Following amenities, accessibility, attractions, and lodging, organizations or groups can be established, and infrastructure in tourist sites can be enhanced. As a result, the SAW approach can be used as a system to help decide which initiatives to prioritize